ANALISIS PENGARUH FAKTOR EKSTERN, PROFITABILITAS DAN PERTUMBUHAN ASSETS TERHADAP KEPUTUSAN PENDANAAN PADA PERUSAHAAN EXPORTERS SETELAH ASEAN FREE TRADE AREA 2015 - Dian Agita; Tri Ratnawati; Saikou Gassama (Jurnal Riset Entrepreneurship, 2020)
This study aims to analyze the influence of external factors, profitability and asset growth on corporate funding decisions in exporters companies listed on the Indonesia Stock Exchange in 2015-2018. The population in this study are exporters companies listed on the Indonesia Stock Exchange with a total of 8 respondents. The analytical tool used in this study is SPSS. The results showed that external factors and profitability directly had a significant effect on capital structure decisions. While the growth of assets does not significantly influence the decision on capital structure.